Perancangan Sistem Pemesanan Stiker Dengan Menggunakan Barcode Berbasis Android (Studi Kasus : PT Indah Kiat Pulp & Paper Tbk) - Eva Yuliza; Ines Heidiani Ikasari (CV. Multi Kreasi Media, 2022)
Barcode is a sign of storing information in the form of expiration date, production code and identity number. In general, the benefits of barcodes obtained are to provide convenience to us. The problem that exists in the current barcode production process is that the barcode design is not in accordance with customer requests (the design is not updated), then the request for fulfillment of production in the field is still manually so that if the team head incorrectly requests an order, it will cause the barcode stock to soar (full stock). and stock defects are not available (data not updated) so stickers that should already exist are remade (double production). Along with the development of current technology, there are many types of Smart Phones to overcome these problems, it is necessary to have a system that supports ease of interaction and can be implemented using the Android system. By utilizing the proposed system correctly, it makes the ordering process easier, saves, and the time used is more effective. With the problems that exist at PT Indah Kiat Pulp & Paper Tbk, namely the sticker ordering system using a barcode, the ordering process is still not computerized. With this barcode creation system, customers can find out a barcode image. With this barcode stock recording system, it will help the admin to find out what production is in the field. With a website, it will make it easier to make and request barcode stickers